5.6q-3.4-4.9q=0.3q-2.3

Simple and best practice solution for 5.6q-3.4-4.9q=0.3q-2.3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5.6q-3.4-4.9q=0.3q-2.3 equation:


Simplifying
5.6q + -3.4 + -4.9q = 0.3q + -2.3

Reorder the terms:
-3.4 + 5.6q + -4.9q = 0.3q + -2.3

Combine like terms: 5.6q + -4.9q = 0.7q
-3.4 + 0.7q = 0.3q + -2.3

Reorder the terms:
-3.4 + 0.7q = -2.3 + 0.3q

Solving
-3.4 + 0.7q = -2.3 + 0.3q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-0.3q' to each side of the equation.
-3.4 + 0.7q + -0.3q = -2.3 + 0.3q + -0.3q

Combine like terms: 0.7q + -0.3q = 0.4q
-3.4 + 0.4q = -2.3 + 0.3q + -0.3q

Combine like terms: 0.3q + -0.3q = 0.0
-3.4 + 0.4q = -2.3 + 0.0
-3.4 + 0.4q = -2.3

Add '3.4' to each side of the equation.
-3.4 + 3.4 + 0.4q = -2.3 + 3.4

Combine like terms: -3.4 + 3.4 = 0.0
0.0 + 0.4q = -2.3 + 3.4
0.4q = -2.3 + 3.4

Combine like terms: -2.3 + 3.4 = 1.1
0.4q = 1.1

Divide each side by '0.4'.
q = 2.75

Simplifying
q = 2.75

See similar equations:

| 3-3(3n-3)=39 | | 3a+9b+-5a+15b= | | 5/9=h/30 | | -8x-2=24-9 | | 8+16p^2=33 | | 85.5/13 | | 9x-4=5x+4 | | 4t+5=-10+t | | v-15=9 | | 63(x-3)=9(x+3) | | 2(x+4)=3x+5 | | 7a+-9b+3a+9b= | | 5x+9=-3 | | O(5)=2(5)-1 | | 8m-7=21+m | | 12q-7=-3q+8 | | -4q=9-5q | | 20a/30+6/30=35/30 | | -5-(-15)= | | 5a^2+30a-11=0 | | -3(3-2n)=5m | | 42+2x=-30+6x | | -8-3h=-h | | 51.8/7 | | 2a+14b+b-7a= | | -5(-5a+3)=11a+5 | | 10x+7y=199 | | -8+9y=10y | | 0=-16x-8x^2-8 | | 3/5x+3=-32 | | 7(-7v+1)=-2v-40 | | 10m=-6+9m |

Equations solver categories